ANALISIS KINERJA KEUANGAN UNTUK MENILAI KESEHATAN BPR SEBELUM DAN SELAMA PANDEMI COVID-19 (STUDI EMPIRIS PADA BPR PERSERODA PATI) - Sherly Erisliana; Agung Prajanto (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
This study was conducted to determine whether there were differences in the financial performance of Rural Bank (BPR) Perseroda Pati before and during the Covid-19 pandemic using CAMELS measurements. The population in this study is Rural Bank (BPR) Perseroda Pati which includes BPR Bank Daerah Pati and BPR BKK Pati in 2019-2021. The sampling method used is a saturated sample, so the sample from this study is following the population. This study uses secondary data in the form of quarterly financial reports. The data analysis technique uses a paired sample t-test with the assistance of IBM SPSS software version 20. The results of this study state that there are no differences in the capital, assets, management, earnings, and liquidity of BPR Perseroda Pati before and during the Covid-19 pandemic.